ANALISIS KANDUNGAN ENZIM DIASTASE PADA MADU SINGKONG HASIL PROSES VACUUM EVAPORATION DAN VACUUM COOLING - Anang Lastriyanto; Silvi Astri Cahyani (Department of Food Technology, Universitas Pasundan, Bandung, 2021)
Honey that has a moisture content above 22% should be done moisture reduction process. reduction of water content is done so that honey does not undergo fermentation and has a longer shelf life. One of the ways that can be used to reduce water content in honey is evaporation. Evaporation is of converting some of the water content in the material into steam by utilizing temperatures close to the boiling point of water. However, the minor content of honey, such as the diastase enzyme, is very sensitive to high temperatures. Therefore, vacuum evaporation is used so that the process uses a lower temperature to minimize the damage to the diastase enzyme. The research method was carried out in 3 stages, namely sampling, evaporation process, and sample testing. The results of this study indicate that the process of vacuum evaporation and vacuum cooling can change the proximate content of cassava honey to comply with SNI.